1977
DOI: 10.1002/bjs.1800640207
|View full text |Cite
|
Sign up to set email alerts
|

Gas gangrene and related infection: Classification, clinical features and aetiology, management and mortality. A report of 88 cases

Abstract: The clinical features of gas gangrene and related infection seen in 88 patients over a 10-year period are described. It is suggested that clostridial infection could be simply classified as either 'gas-forming' or 'non-gas-forming'. The gas-forming group represents the more severe form of infection. Non-clostridial gas gangrene may present in a variety of forms. The anaerobic streptococcus was the organism most frequently responsible, but these cases were indistinguishable from clostridial infection on clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
4
2

Year Published

1983
1983
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(47 citation statements)
references
References 33 publications
0
39
4
2
Order By: Relevance
“…Others have found that trauma patients developing gas gangrene have a better prognosis than patients developing gas gangrene after elective operations (Roding et al 1972). However, this difference could not be confirmed by Darke et al (1977), or by the present series. Thus the mortality rate after gas gangrene of the extremities seems to lie between 8 and 13 percent in reports from Holland et al (1975), Trippel et al (1967) and Darke et al (1977) all of whom used surgical measures, antibiotics and hyperbaric oxygen treatment.…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…Others have found that trauma patients developing gas gangrene have a better prognosis than patients developing gas gangrene after elective operations (Roding et al 1972). However, this difference could not be confirmed by Darke et al (1977), or by the present series. Thus the mortality rate after gas gangrene of the extremities seems to lie between 8 and 13 percent in reports from Holland et al (1975), Trippel et al (1967) and Darke et al (1977) all of whom used surgical measures, antibiotics and hyperbaric oxygen treatment.…”
Section: Discussioncontrasting
confidence: 97%
“…However, this difference could not be confirmed by Darke et al (1977), or by the present series. Thus the mortality rate after gas gangrene of the extremities seems to lie between 8 and 13 percent in reports from Holland et al (1975), Trippel et al (1967) and Darke et al (1977) all of whom used surgical measures, antibiotics and hyperbaric oxygen treatment. In contrast to these reports Altemeier & Fullen (1971) avoided the use of hyperbaric oxygen treatment and presented a mortality rate of 15 per cent in 54 patients with myonecrotic gas gangrene.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations